PROFILE OF PATIENTS WHO RECEIVE CARDIAC CATHETERIZATION: SUPPORT FOR PREVENTION OF CARDIOVASCULAR RISK FACTORS - Solange Meira de Sousa; Elizabeth Bernardino; Rozeli Maria Mateus Vicelli; Carmen Elizabeth Kalinowski (Universidade Federal do Paraná, 2014)
This descriptive, transversal study, with a quantitative approach, aimed to identify the profile of the patients who received cardiac catheterization in the Interventional Cardiology Department in a teaching hospital. For a period of six months, the procedures were monitored using a checklist-type questionnaire. The study included procedures scheduled for patients receiving inpatient and outpatient treatment in the hospital, excluding emergency procedures. The results indicated the predominance of male patients, patients aged between 62-69 years old, hypertension, dyslipidemia and diabetes. The identification of the profile contributes to the development of prevention strategies against risk factors for coronary artery diseases and, in this regard, the work of the nursing team becomes decisive.